Are patients accurate forecasters of their emotional response to medical conditions? A scoping review on affective forecasting - Y M Smulders; R Otten; Claudi Bockting; G J van den Bosch; R A N Roos (BMJ Open)
Objective In this paper, we challenge the premise that patients are capable of accurately predicting their emotional response or quality of life in anticipation of health changes. Our goal was to systematically review the published empirical evidence related to the reliability of affective forecasting in the context of medical conditions.Design Scoping review.Setting We conducted a search string using both simple search terms as well as MeSH terms and searched the electronic databases of PubMed, Embase, CINAHL and Cochrane up to April 2021.Participants We initially selected 5726 articles. Empirical studies reporting on predicted and/or observed emotions or quality of life concerning deterioration, improvement in health or chronic illnesses were included. Furthermore, empirical studies of healthy individuals predicting emotional response or quality of life compared with patients reflecting on emotions or quality of life concerning deterioration or improvement in health or chronic illnesses were also included. Studies on healthy participants, psychiatric patients and non-English articles were excluded.Results 7 articles were included in this review. We found that patients generally tend to systematically exaggerate both anticipated happiness and sorrow/grief after health improvement and deterioration, respectively.Conclusion Patients are less adept in predicting emotional response or quality of life regarding to health changes than we are inclined to assume. We discuss several biases which could explain this phenomenon. Our findings are relevant in the context of treatment decisions, advanced care planning and advanced care directives.